Microbial interactions associated with indigenous fermented milk - Coetzer, Shirleen Mari (University of the Free State, 2012)
Fermented foods contain essential nutrients needed to maintain optimum health as well as other components that help in the delaying and prevention of diseases such as chronic illnesses. Indigenous naturally fermented milk of different regions in Africa play an important role in their daily diet and it helps rural woman to generate a household income. The literature review focused on the microbial composition of fermented milk in different regions in Africa (Botswana, Lesotho, Namibia and Swaziland). Furthermore, the positive and negative interactions associated with fermented milk were discussed in detail. Fermented milk is the result of the activity of a group of microorganisms. Each of these organisms plays an important role in the production of the final fermented product. Before fermentation, undesired microorganisms were present in the samples, but after a four day fermentation the yeasts and lactic acid bacteria (LAB) interactions created an environment impossible for pathogens to survive. The yeasts provide essential growth compounds for the starter culture (LAB) but remained at low numbers at the end of fermentation because of being outcompeted by faster growing LAB. The dominant LAB of the different regions was determined by DGGE and culture sequencing. Enterococci and Lactoccoci were found to be the dominant LAB followed by Leuconostocs and Streptococci. Enterococcus durans species comprised 32% of the isolated LAB. The microbial composition has beneficial effects not only for the consumer but may assist in the improvement of the final product. The microbial interaction between dominant LAB and yeasts frequently observed in dairy products was also monitored during a study in Lesotho. During the growth studies the LAB in combination with the yeasts had a much better growth rate, but in contrast the yeasts grew better on its own compared to those in combination with LAB. For the change in chemical composition it was also found that if in co-culture more organic acids were produced resulting in a rapid decrease in pH levels. During fermentation a small number of LAB proofed to have antagonistic effects against a series of pathogenic bacteria and were further evaluated by evaluating the fermentation process of milk of Lesotho and the LAB's inhibition effect. Salmonella anterica, Shigella sonnei, Staphylococcus aureus and Escherichia coli were completely inhibited by Lactobacillus plantarum and Enterococcus mundtii/feacium. Further studies need to be done in the isolation of novel lactic acid bacteria to provide insight on the preservation and safety of fermented milk products.

Gefermenteerde voedsel besit belangrike nutriente wat nodig is vir 'n optimal gesondheid, dit besit ook ander komponente wat help in vertraaging en voorkoming van kronies siektes. Inheemse natuurlike gefermenteerde melk van verskillende gebiede in Afrika speel 'n belangrike rol in die daaglikse diet en help landelike vrouens om 'n huislike inkomste by te dra. Die literatuur oorsig fokus op die mikrobiese komposisie van gefermenteerde melk in verskillende gebiede in Afrika (Botswana, Lesotho, Namibia en Swaziland). Die positiewe en negatiewe interaksies geassosieer met gefermenteerde melk word ook volledig bespreek. Gefermenteerde melk is die resultaat van die aktiwiteite van 'n groep mikroörganismise. Elk van die organismis speel 'n belangrike rol in die vervaardiging van die finale gefermenteerde projek. Voor fermentasie kom onplesierige mikroörganismis voor in die produk, maar na fermentasie vorm die giste en melksuurbakterieë 'n omgewing wat dit onmoontlik maak vir patogene om te oorleef. Die giste voorsien vir die begin kultuur (melksuurbakterieë), maar aan die einde van fermentasie kom die giste slegs voor in lae getalle as gevolg van die melksuurbakterieë wat vinniger groei. Die dominante melksuurbakterieë van die verskillende gebiede was bepaal deur DGGE en kultuur basispaaropeenvolgingbepalings. Enterococci en Lactococci was die dominante melksuurbakterieë gevolg deur Leuconostocs en Streptococci. Enterococcus durans spesies bestaan uit 32% van die geïsoleerde melksuurbakterieë. Die mikrobiese samestelling het 'n voordelige effek nie net vir die verbruiker nie maar help ook in die bevordering van die finale produk. Die mikrobiese interaksies tussen die dominante melksuurbakterieë en die giste wat gereeld gevind word in suiwel produkte is ook gemonitor. Tydens die groei studies van die melksuurbakterieë in kombinasie met die giste het die melksuurbakterieë 'n baie beter groei tempo, maar in kontras the giste groei beter op hulle eie as in kombinasie met melksuurbakterieë. Vir die verandering in die chemiese komposisie is daar gevind dat wanner in mede-kultuur daar meer organiese sure geproduseer word en dat die pH ook verlaag wat duidelik aandui dat die giste dra by tot die vermenigvuldige optimale groei van die melksuurbakterieë. Tydens fermentasie is dit bewys dat 'n klein hoeveelheid melksuurbakterieë antagonistiese effek kan uit oefen teen a reeks patogeniese bakterieë en is verder geevalueer deur die fermentasie proses van die melk van Lesotho en die melksuurbakterieë inhibisie effek te monitor. Salmonella anterica, Shigella sonnei, Staphylococcus aureus en Escherichia coli was heeltemal geinhibeer deur Lactobacillus plantarum en Enterococcus mundtii/feacium. Verder studies moet nog gedoen word op die isolasie van nuwe melksuurbakterieë om insig te kry op die preservasie en veiligheid van gefermenteerde melk produkte.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2012
Keywords: Africa indigenous milk; Fermented; Microbial interactions; Lactic acid bacteria; Pathogenic inhibition; Microbial diversity; Milk -- Microbiology